PENGEMBANGAN SENAM BOLA BERKARAKTER UNTUK MATERI PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN SISWA SEKOLAH DASAR - Donny Anhar Fahmi, Osa Maliki (Universitas PGRI Semarang, 2015)
In the process of study in physical education,sport, and health for elementary school student, gymnastic ball characteris can used as one of matery in rhitmic activity for V class. Will hoped to add the variety in physical education,sport, and health material which limited variety. This research becomes the development f the research it self. The procedures of this research which is used consist of the analysis of product which is developed, to improve product earlier, the expert validation, the field trial, consist of the small groupt test and the big group test, product revision, and the development product resultThe research result is a product model for gymnastic ball charactercan be used as media learning of?é?á physical education,sport, and health. Based on the scale wide test to the product, the using of gymnastic ball charactermodel to the student, it can increase the pulse for about 62% from 120 student. From the response which is given to 120 student to the psycomotor aspect which including in a good category as much as 94 student, middle category as much as 23 student, and low category as much as 3 student. For Cognitive aspect including a good category as much as 81 student, middle category as much as 34 student, and low category as much as 5 student. Affective aspect which including good category as much as 88 student, middle category as much as 26 student, and low category as much as 6 student.Based on the researh result which is concluded?é?á: (1) The development of gymnastic ball charactermodel for learning physical education,sport, and health elementary school students can be increase physical activity student in learning. Improvement pulse rate that happened?é?á of students until 62 %. This matter is knowable from means of pulse rate before learning gymnastic ball characteris 93 times a minut, and experiencing of improvement until 150 times a minut after following learn aerobic gymnastic. (2) The student is very intersting and feels happy with the gymnastic ball charactermodel which is thaugt so that the student can move effectively in learning implementation.